2012
DOI: 10.1166/jnn.2012.6498
|View full text |Cite
|
Sign up to set email alerts
|

One-Atmosphere Aqueous-Solution Synthesis of Trimolybdate Nanomaterials and the Feasibility for Mass Production

Abstract: Mass production of low-cost functional nanomaterials is an important issue for the development of nanoscience and nanotechnology. With rich structural, physical and chemical properties, polyoxometalates are important functional materials for both industrial applications and fundamental research. We presented a family of alkali trimolybdate nanowires and nanorods that were synthesized by a one-atmosphere aqueous solution method from a mixture of two solutions, one consisting of (NH4)6Mo7O24 x 4H2O and the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It showed that, under the conditions of our experiments, the minimum concentration of Ag + ion concentration for antibacterial application was somewhere between 18 ppm and 7 ppm, a value much higher than the 1.7±0.3 ppm measured from the suspensions of Ag-doped NWs. Therefore, the results have shown that the tiny amount of Ag + ion released in aqueous solutions from the solid Ag-doped NWs is not the major antibacterial factor observed in our experiments [32,33]. The aqueous solution of Ag + ions is known as a strong antibacterial agent.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…It showed that, under the conditions of our experiments, the minimum concentration of Ag + ion concentration for antibacterial application was somewhere between 18 ppm and 7 ppm, a value much higher than the 1.7±0.3 ppm measured from the suspensions of Ag-doped NWs. Therefore, the results have shown that the tiny amount of Ag + ion released in aqueous solutions from the solid Ag-doped NWs is not the major antibacterial factor observed in our experiments [32,33]. The aqueous solution of Ag + ions is known as a strong antibacterial agent.…”
Section: Resultsmentioning
confidence: 73%
“…The suspension was stirred thoroughly, kept for 24 hrs and filtered with a 0.45 μm-pore filter. In the suspension the concentration of Ag-doped NWs (1 wt%) was much higher than its minimum inhibitory concentration observed previously for antibacterial effect, which was 2-15 ppm [32,33]. This setup ensured that, if Ag + ions could be released from the Ag-doped NWs, in the filtered solution one should found enough Ag + ions, and the solution should have obvious antibacterial effect.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…We have followed the method reported previously to synthesize the trimolybdate NWs [11,12]. We first examined the antibacterial effects of K 2 Mo 3 O 10 •3H 2 O, and found its unique effect on Cuyitococcus Neofonmans (Cne).…”
Section: Methodsmentioning
confidence: 99%